A Review on the Development of Spectroscopic Sensors for the Detection of Creatinine in Human Blood Serum : Life Sciences-Chemistry for New drug discovery - Krishanu Sarkar (International Journal of Life Science and Pharma Research, 2022)
Creatinine measurement is the key parameter in detecting renal, muscular and thyroid dysfunction. The accurate detection of creatinine level may be informative regarding the functional processes of these systems and help in early detection of acute diseases.There are lots of techniques available for detecting creatinine in human blood serum, most of them are of mainly based on spectroscopic (spectrophotometry, colorimetry and fluorimetric). Other techniques are based on electrochemical, impedometrical, Ion Selective Field-Effect Transistor (ISFET) and chromatography techniques. Each method has its own advantages and few limitations(limitation would be better word) regarding selectivity, sensitivity, reproducibility, cost effective, point-of-care level detection etc. Few methods based on electrochemical techniques are recently promising in detecting creatinine at the point-of-care level with adequate sensitivity and selectivity. On the other hand some biosensors based on spectroscopic techniques are recognized as the most promising substitute in recent years. As creatinine levels in the blood serum offer better information about patient status, here in this review it is thoroughly discussed over other biological samples such as urine, saliva.